EVALUASI PENGELOLAAN BARANG MILIK DAERAH (STUDI PADA PEMERINTAH KABUPATEN CILACAP) - Earlyninda Ayu Listyanti (ABIS: Accounting and Business Information Systems Journal, 2015)
The purpose of this study is to evaluate the management of local property in the Government of Cilacap Regency. The result of the evaluation resulted in the suitability of the management of regional property in the Government of Cilacap Regency with Permendagri Nomor 19 Tahun 2016 on the guidance of the management of regional property, the factors causing the problem of management of local property in Cilacap Regency, and giving recommendation improvement for the management of the property area. The result of the observation states that there is an increase in the suitability of the management of regional property in the Government of Cilacap Regency from 2015 to 2016. From the interviews, the factors causing the problem of management of regional goods are among others Human resources, leadership, management of regional property, system, Inspectorate of Cilacap Regency Government, and BPKP